Perlindungan Hukum terhadap Perusahaan sebagai Pemilik Rahasia Dagang dalam Hal Berakhirnya Hubungan Kerja - Nadya Utari (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
In accordance with Indonesia's Trade Secret Law, the proprietor of any technological or business information that is both uncommon and of economic value is obliged to maintain its confidentiality. It is incumbent upon companies to enter into specific agreements with employees who are privy to this information, with the objective of preventing leaks. The case studies of PT AIA Financial and PT 3D Garmentech illustrate the significance of legal protection and dispute resolution in the context of corporate data leaks. This research employs a qualitative analysis of the issue, utilizing both secondary and primary data and normative legal methods. This research concludes that the owner of a trade secret is entitled to exclusive use and licensing of the trade secret, and may prohibit other parties from using or disclosing such information for commercial purposes, in accordance with Article 4 of the UURD. In the event of a leak, disputes can be resolved through non-litigation channels or, in the event that these prove ineffective, through closed-door courts. A variety of legal protections are available to owners of trade secrets, including the use of confidentiality agreements with employees and the initiation of civil suits for compensation. Additionally, criminal law offers protection, as delineated in Articles 16 and 17 of the UURD. The drafters of the UURD vested the state with the authority to enforce compliance with trade secret legislation.